Surgical acute abdomen in the elderly. Hospital Nacional Daniel Alcides Carrión - Callao - 1992-1996 - Arrus Soldi, José (1997)
The aim of this descriptive and retrospective study was to assess the main causes leading to Surgical Acute Abdomen (S.A.A.) in the elderly, as well as their clinical manifestations and morbi-mortality. All individuals older than 60 years which were admitted with the diagnosis of S.A.A. and underwent surgery at the emergency room of the Hospital Nacional Daniel A. Carión (HNDAC) between january 1th, 1992 and december 31th, 1996, were considered. There were 317 cases of S.A.A. in elderly patients during the study period, which represents 3,33% of all surgical interventions performed by the emergency staff. Mean age was 72,0 years, and there were a predominance of male sex (59,3%). The most frequent causes of S.A.A. were intestinal obstruction (43,5%), acute appendicitis (18,9%), acute cholecystitis (12,9%) and visceral perforation; inflammatory processes make a total of 45,4%. External hernias, bridles and adherences, and colonic volvulus were the more frequent causes of intestinal obstruction. 53,3% of patients with appendicitis, developed peritonitis. Most of patients with acute cholecystitis had advanced forms (pyocholecystitis, gangrene, perforation). Abdominal pain was the commonest symptom for all entities (100%), while fever, guarding and peritoneal signs were less frequent in our patients. Global morbility rate was 50,4%, being the cases which come from operatory issues more frequent (68,7%), and among them, surgical wound infection an important cause. Global mortality rate was 12,1%, being septic shock the commonest cause (70,4%), mainly those from abdominal source (68,4%).